(untitled) (International Journal of Innovative Computing, 2014)
Dynamic parameterized states tracking workflow system is a workflow solution which aims to decouple business logic and application code in order to minimize rigid or spaghetti code in any kind of workflow system. This approach, allows programmer to focus on the development of the application itself, and let the business process owner to deal with the application data, business rules and logic. Business process owner can setup, configure and deploy workflow process independently without changing the workflow engine application code. This workflow engine is featured with dynamic functions calling, task aging checking and reminder sending. These specific features allow process owner to customize their flows seamlessly with their business requirement using this workflow engine. The proposed workflow solution can be library package or SOA based, and can further configure to be multitenant workflow solution. In this paper, the design of proposed workflow solution is discussed. Actual live systems, Intellectual Property Management System (IPMS) and Human Resource Information System (HRIS) which have already using the proposed workflow solution are also showcased in this paper.